2019
DOI: 10.3390/ma12101646
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Forming and Surface Engineering of Disc Springs by Inducing Residual Stresses by Incremental Sheet Forming

Abstract: Disc springs are conical annular discs, which are characterized by a high spring force with a small spring travel and good space utilization. In operation, they must meet high demands on the stability of the spring characteristic and the fatigue strength. Under loading, tensile stresses occur which limit the possible applications of disc springs. Compressive stresses can be generated in the stressed areas by means of shot-peening in order to extend the operating limits for a given yield and fatigue strength. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…During the ISF operation, the sheet blanks are deformed locally by a small hemispherical tool along the designated path. Hajavifard et al [23] and Maqbool et al [22] concluded in their work that TPIF with a negative die is the best-suited variant for the forming of disc springs.…”
Section: Incremental Sheet Metal Formingmentioning
confidence: 99%
See 1 more Smart Citation
“…During the ISF operation, the sheet blanks are deformed locally by a small hemispherical tool along the designated path. Hajavifard et al [23] and Maqbool et al [22] concluded in their work that TPIF with a negative die is the best-suited variant for the forming of disc springs.…”
Section: Incremental Sheet Metal Formingmentioning
confidence: 99%
“…Two strategies for the targeted generation of residual stresses in MASS disc springs by ISF were proposed in previous studies [12,22,23]. The effect of the ISF process parameters, i.e., the forming tool diameter, feed rate, and step-down, on the generated residual stresses are investigated in detail using X-ray diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…Although residual stresses have an impact on geometric accuracy of formed components and their service life, only a limited amount of studies have been reported in the literature that deals with the ISF process and residual stresses. Furthermore, to the knowledge of authors, no study has been reported in the literature that focuses on the targeted utilization of the residual stresses of the ISF process other than the recent studies reported by the authors [6][7][8][9]. In the next section, a brief review of the literature dealing with the SPIF process and the residual stresses is presented.…”
Section: Introductionmentioning
confidence: 98%
“…Hajavifard et al [30] used ISF to improve properties of conical annular discs by introduction residual stresses in material. The main mechanism of residual stress generation was the transformation of metastable austenite into martensite under the action of the forming tool.…”
Section: Introductionmentioning
confidence: 99%